Pitfalls of conducting and interpreting estimates of energy availability in free-living athletes - Burke, L. M.; Lundy, B.; Fahrenholtz, I. L.; Melin, A. K. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
The human body requires energy for numerous functions including, growth, thermogenesis, reproduction, cellular maintenance, and movement. In sports nutrition, energy availability (EA) is defined as the energy available to support these basic physiological functions and good health once the energy cost of exercise is deducted from energy intake (EI), relative to an athlete`s fat-free mass (FFM). Low EA provides a unifying theory to link numerous disorders seen in both female and male athletes, described by the syndrome Relative Energy Deficiency in Sport, and related to restricted energy intake, excessive exercise or a combination of both. These outcomes are incurred in different dose-response patterns relative to the reduction in EA below a "healthy" level of ~45 kcal·kg FFM-1·day-1. Although EA estimates are being used to guide and monitor athletic practices, as well as support a diagnosis of Relative Energy Deficiency in Sport, problems associated with the measurement and interpretation of EA in the field should be explored. These include the lack of a universal protocol for the calculation of EA, the resources needed to achieve estimates of each of the components of the equation, and the residual errors in these estimates. The lack of a clear definition of the value for EA that is considered "low" reflects problems around its measurement, as well as differences between individuals and individual components of "normal"/"healthy" function. Finally, further investigation of nutrition and exercise behavior including within- and between-day energy spread and dietary characteristics is warranted since it may directly contribute to low EA or its secondary problems.